Rewards for Patents and Inventor Behaviors in Industrial Research and Development - Giarratana, Marco S.; Mariani, Myriam; Weller, Ingo (Academy of Management Journal, 2018)
This study investigates the effects of rewards in a research and development (R&D) setting in which employees’ inventive efforts lead to patented inventions. Pay for performance (PFP) for inventions is associated with two challenges: Low-quality inventions may be rewarded (false positives), and high-quality inventions may be overlooked (false negatives). Building on previous findings regarding the motivational and informational effects of rewards, we use social identity theory to predict that different types of inventors react differently to such false positive and false negative information. Specifically, we hypothesize that PFP that produces false positives has detrimental effects on corporate inventors with a taste for science, who are motivated by scientific prestige, reputation, and intellectual curiosity. The empirical results from survey data related to 3,995 inventor–patent pairs show that, for this particular group of inventors, false positives are associated with reduced effort in research activities and fewer interactions with peers in the R&D department. In addition, these effects are stronger when firms have many patents and thus provide less noisy information to corporate inventors.